Nuclear pore complex plasticity during developmental process as revealed by super-resolution microscopy. Issue 1 (December 2017) - Sellés, Julien; Penrad-Mobayed, May; Guillaume, Cyndélia; Fuger, Alica; Auvray, Loïc; Faklaris, Orestis; Montel, Fabien
Abstract Nuclear Pore Complex (NPC) is of paramount importance for cellular processes since it is the unique gateway for molecular exchange through the nucleus. Unraveling the modifications of the NPC structure in response to physiological cues, also called nuclear pore plasticity, is key to the understanding of the selectivity of this molecular machinery. As a step towards this goal, we use the optical super-resolution microscopy method called direct Stochastic Optical Reconstruction Microscopy (d STORM), to analyze oocyte development impact on the internal structure and large-scale organization of the NPC. Staining of the FG-Nups proteins and the gp210 proteins allowed us to pinpoint a decrease of the global diameter by measuring the mean diameter of the central channel and the luminal ring of the NPC via autocorrelation image processing. Moreover, by using an angular and radial density function we show that development of theXenopus laevis oocyte is correlated with a progressive decrease of the density of NPC and an ordering on a square lattice.